Litter decomposition rate of mangrove forest in the tourism area of pariaman city - Mutiara Ardiana; Irma Leilani (Jurnal Serambi Biologi, 2022)
Mangrove ecosystems are located in coastal areas that are affected by the tides of sea. Mangrove forest acts as a green belt that protects the coast from erosion due to ocean waves or tsunami storms and traps sediments as accretionary activity. One of the processes that occur in the mangrove ecosystem that contributes the most to water fertility is the process of decomposition or destruction of mangrove litter. Litter destruction is part of the decomposition process stage that can produce important nutrients in the food chain through the productivity of the waters around the mangrove forest. The purpose of the study was to determine the rate of decomposition of mangrove litter in the Pariaman Mangrove Forest Tourism Park. This descriptive study was conducted from November 2021 -February 2022. This study used the litter-bag method to store leaf litter for which the rate of decomposition will be calculated. The results showed that the rate of decomposition based on the time of observation at the research station was different. At Station 1, the final dry weight value is smaller than Station 2 and Station 3, namely 0,26 gr/day at Station I, 0.9 gr/day at Station II, and 1,3 gr/day at Station 3.